Onset of Workplace Bullying and Risk of Weight Gain: A Multicohort Longitudinal Study. Issue 11 (14th September 2020) - Xu, Tianwei; Magnusson Hanson, Linda L.; Clark, Alice J.; Ersbøll, Annette K.; Westerlund, Hugo; Madsen, Ida E. H.; Rugulies, Reiner; Pentti, Jaana; Stenholm, Sari; Vahtera, Jussi; Sørensen, Jeppe K.; Nordentoft, Mads; et al.
Abstract : Objective: This study aimed to examine the onset of workplace bullying as a risk factor for BMI increase. Methods: Repeated biennial survey data from three Nordic cohort studies were used, totaling 46, 148 participants (67, 337 participant observations) aged between 18 and 65 who did not have obesity and who were not bullied at the baseline. Multinomial logistic regression was applied for the analysis under the framework of generalized estimating equations. Results: Five percent reported onset of workplace bullying within 2 years from the baseline. In confounder‐adjusted models, onset of workplace bullying was associated with a higher risk of weight gain of ≥ 1 BMI unit (odds ratio = 1.09; 95% CI: 1.01‐1.19) and of ≥ 2.5 BMI units (odds ratio = 1.24; 95% CI: 1.06‐1.45). A dose‐response pattern was observed, and those exposed to workplace bullying more frequently showed a higher risk ( P trend = 0.04). The association was robust to adjustments, restrictions, stratifications, and use of relative/absolute scales for BMI change. Conclusions: Participants with exposure to the onset of workplace bullying were more likely to gain weight, a possible pathway linking workplace bullying to increased long‐term risk of type 2 diabetes.